The biochemical effects and histological features of oral administration of stingless bee honey (heterotrigona itama) on diabetic sprague-dawley wound rats model - Ismail, Anis Farihan (2023)
Diabetes mellitus (DM) has emerged into a major and growing public health issue. The morbidity and mortality rate of DM has increased due to its complications, including pancreatic damage, diabetic nephropathy (DN), and hepatocellular damage as well as impaired wound healing. According to various research, honey consumption is inversely related to the risk of developing diabetes. However, it still not be emphasize by the medical practitioner, due to debate on glycemic control in individual with honey supplementation. Therefore, the current study was carried out to examine the effects of oral administration of stingless bee honey (SBH) on the management of DM in order to emphasize the significance of SBH in the treatment of diabetic. Sixty male Sprague-Dawley (SD) rats were induced with intraperitoneal injection of streptozotocin (STZ) (50 mg/kg) to become DM. They were divided into five main groups according to treatment given. Non-diabetic rats (ND) and diabetic untreated rats (UNT) were orally gavage with normal saline. While, the SBH dosage of 2.0 g/kg, metformin (MET) 250 mg/kg and the combination of both SBH and MET (SBME) were administered through oral gavage to determine their effects on diabetic rats and to assess the wound healing progress compared to ND rats as controlled. For each main group, excisional wound (open wound) and incisional wound (close wound), n=6 for each wound, were created to mimic wound in diabetic patient. The dose of 2.0 g/kg SBH for 12 consecutive days exhibited antidiabetic activity by significantly lowering fasting blood glucose (FBG) in diabetic rat models. Furthermore, SBH give a lower level of oxidative stress marker (MDA), pro-inflammatory marker (IL-6), coupled together with higher level of IL-10 in EW and IW groups. The level of serum C-peptide, insulin and lipid profile were not significantly difference in all group of rats in EW and IW. Pancreatic cells of SBH-treated diabetic rats showed regeneration of islets after stained with haematoxylin & eosin (H&E) and periodic acid-Schiff (PAS). The serum creatinine and urea level showed insignificant different among groups but the rat kidney of SBH group showed thin layer of glomeruli basement membrane and less hydropic changes as compared to other groups (EW and IW). Although the reduction in serum ALT, AST and ALP was not significant but histologically, treatment with SBH improved the hepatic cells and reduced the formation of fatty vacuoles and dilatations of blood sinusoids in the liver of diabetic rats as compared to other groups. SBH also significantly accelerated the wound closure and give a higher wound contraction percentage in DM rats. In conclusion, administration of SBH (2.0 g/kg) for 12 days has shown significant improvement in glycemic controlled (FBG), give low level of IL-6 and MDA as well as higher level of IL-10 as compared to other treated groups (EW and IW). It also improve the histological features of pancreas, kidney and liver as well as promote wound healing of diabetic rats.